The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.seizure.2007.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge and attitudes towards epilepsy in Jordan

Abstract: The overall knowledge and attitudes of Jordanians towards epilepsy is relatively comparable with the results from Asian countries but more negative when compared with reports from the Western countries. Consequently, well-organized educational campaigns are needed to improve public perception about epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
9
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 13 publications
7
38
9
2
Order By: Relevance
“…The belief in the evil spirit and the belief in the evil eye were both statistically significantly higher among students of humanities and students with a low SEI. Our results are consistent with previous studies in which components of the SEI (education, income, or employment status) predicted knowledge about epilepsy and attitudes toward PWE [9,11,18,19]. Previous studies also showed differences in knowledge and health habits between students of humanities and those of scientific faculties [35].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The belief in the evil spirit and the belief in the evil eye were both statistically significantly higher among students of humanities and students with a low SEI. Our results are consistent with previous studies in which components of the SEI (education, income, or employment status) predicted knowledge about epilepsy and attitudes toward PWE [9,11,18,19]. Previous studies also showed differences in knowledge and health habits between students of humanities and those of scientific faculties [35].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, this percentage is less than that reported in the study conducted among the Jordanian public (about 88%) [11]. There was, however, a selection bias in that study as more than one-third of the participants (39%) had a health-care-related occupation.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations